BIOMASS AND CARBON ASSESSMENT IN TWO TREE SPECIES IN A CLOUDY FOREST - Acosta Mireles, Miguel; Carrillo Anzures, Fernando; Gómez Villegas, Raúl Gilberto (Revista Mexicana de Ciencias Agrícolas, 2018)
The generation of allometric equations is important to determine biomass and carbon in tree species. This information is useful in climate change studies. In this paper, allometric equations were generated for two species of ecological importance in the cloud forest: Clethra mexicana DC and Alnus arguta (Schltdl) Spach. Equations determined are of the form Y= bXk; where: Y= biomass or carbon content (kg); and X= normal diameter (ND) in
Keywords: Alnus arguta (Schltdl) Spach; Clethra mexicana DC; carbon store; allometric equations